Efeitos do fogo sobre comunidades de aves no Pantanal Mato-Grossense - Ubaid, Flávio Kulaif [UNESP] (2014)
Pantanal is the largest wetland on the planet and supports a considerable portion of the South American biodiversity. Throughout its history of human occupation, fire was widely used as the main method of soil management, and currently is one of the main threats to the ecosystem. The present study evaluated the impact of fire on birds and on the vegetation of three physiognomies of Pantanal (two dry forests ‐ acurizal and tabocal; and a floodplain forest – cambarazal), and determined how the vegetation structure influenced the bird assemblage of these plant formations pre and post‐fire. The study was conducted at the RPPN SESC Pantanal, located in north Pantanal. In each forest, the bird assemblage was sampled in two areas, one area burned in 2005 and an unburned one. A third area, burned in 2010, was sampled in cambarazal. Birds were sampled between 2011‐2013 by point counts and mist netting. In each sampling point, parameters associated with the vegetation structure were estimated and correlated with bird assemblage. Fire reduced the number of species and the total bird abundance in acurizal, while in tabocal and cambarazal, no significant differences were found. More birds were affected in acurizal (31%), while in tabocal and cambarazal, this proportion was lower (15 and 10%). Specialist insectivores and frugivores were the most affected groups in the three habitats. Proportionally, few species benefited by the fire, mainly generalist birds and typical of more open areas, while most were significantly different among treatments. The fire burned large trees and changed several structures in the habitat, that in turn affected the bird assemblage of each type of forest differently. Thus, the fire was a defining factor in the bird assemblage of the tree forests examined. However parameters such as richness and abundance did not provide a clear picture of these effects. In future management actions, mature forests should ...